Influence of accounting information systems and budget towards service quality (case study on BPJS patients at Sidamulya Health Center, Brebes) - Slamet Bambang Riono; Solikhin; Dumadi; Anisa Sains Kharisma (Institute of Computer Science (IOCS), 2023)
This study aims to analyze the effect of accounting information systems and budgets on the quality of service at the Sidamulya Brebes Health Center. The author uses a descriptive research method using a qualitative research approach. Data collection techniques consist of interviews, observations and literature studies. Research data in the form of primary data with questionnaire instruments. The population of this study was 4,598 patients participating in registered active health insurance users. The study sample was determined 98 people, with the Slovin formula, the margin of error is 10%. Data analysis techniques with multiple linear regression assisted by SPSS. Instruments are tested with validity and reliability. Some of the data analysis tests in this study are classical assumption tests including normality tests, multicollinearity tests, heterokedasticity tests, and descriptive static tests. Hypothesis tests include statistical tests t, statistical tests F, and coefficient of determination (R2) tests. The results of this study show that the accounting information system has a positive and significant effect on service quality with t table 4.306 > t calculate 1.98525 and Sig. value 0.000, budget expenditure has a positive and significant effect on service quality with t table 2.055 > t calculate 1.98525 and Sig. value 0.043, and accounting information systems and budgets simultaneously have an influence on the quality of service for BPJS Puskesmas Sidamulya Brebes patients by 32.1%.